Treeline advances along the Urals mountain range - driven by improved winter conditions? - Hagedorn, Frank; Shiyatov, Stepan G.; Mazepa, Valeriy S.; Davi, Nadezhda M.; Grigor`ev, Andrey A.; Bartysh, Alexandr A.; Fomin, Valeriy V.; Kapralov, Denis S.; Terent'ev, Maxim; Bugmann, Harald; Rigling, Andreas; Moiseev, Pavel A. (Global Change Biology, 2014)
ISSN:1354-1013 ISSN:1365-2486